Estimates Committee 1957 - 58 Twenty-First Report(Second Lok Sabha) - Planning Commission (Planning Commission, 1958)
The Conference appointed a National Planning Committee with Pt. Jawaharlal Nehru as Chairman. The National Planning Committee appointed several sub-committees to study different aspects of the national economy. A number of reports were prepared keeping in view the object of attaining national self-sufficiency for the country and doubling the standard of living in ten years. This Committee succeeded in making the people planning conscious.
Lok Sabha Secretariat
Lok Sabha Secretariat